2022
DOI: 10.7717/peerj.13090
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus time course infection of human macrophages reveals intracellular signaling pathways relevant to repurposed therapeutics

Abstract: Background Chikungunya virus (CHIKV) is a mosquito-borne pathogen, within the Alphavirus genus of the Togaviridae family, that causes ~1.1 million human infections annually. CHIKV uses Aedes albopictus and Aedes aegypti mosquitoes as insect vectors. Human infections can develop arthralgia and myalgia, which results in debilitating pain for weeks, months, and even years after acute infection. No therapeutic treatments or vaccines currently exist for many alphaviruses, including CHIKV. Targeting the phagocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…We sorted the results so that drug targets present in multiple signaling pathways would be ranked higher ( Table 6 ). Though Pathways2Targets results are in no way conclusive of drug efficacy for a novel indication, the algorithm provides a short-list of drugs for subsequent validation in the laboratory and has a track record of returning many drugs already in use for a given disease and several novel drug candidates [ 44 - 47 ]. Based on the Pathway2Targets output, we predicted the most relevant existing FDA-approved drugs for other indications that could affect the lymphoma phenotype are Doxycycline, Ocriplasmin, and Collagenase.…”
Section: Resultsmentioning
confidence: 99%
“…We sorted the results so that drug targets present in multiple signaling pathways would be ranked higher ( Table 6 ). Though Pathways2Targets results are in no way conclusive of drug efficacy for a novel indication, the algorithm provides a short-list of drugs for subsequent validation in the laboratory and has a track record of returning many drugs already in use for a given disease and several novel drug candidates [ 44 - 47 ]. Based on the Pathway2Targets output, we predicted the most relevant existing FDA-approved drugs for other indications that could affect the lymphoma phenotype are Doxycycline, Ocriplasmin, and Collagenase.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the enrichr pathway enrichment software only required a gene symbol, log 2 fold-change values, and FDR-adjusted p -values as input from the DEG list. The statistically significant differentially expressed genes (DEGs; FDR-corrected p -value < 0.05) were then subjected to signaling pathway analysis using the Signal Pathway Impact Analysis (SPIA) algorithm with 3,000 bootstrap replicates to generate a null distribution for each of over 2,000 public signaling pathways ( Tarca et al, 2009 ), as reported previously ( Scott, Jensen & Pickett, 2021 ; Gray et al, 2022 ; Moreno et al, 2022 ; Rapier-Sharman, Clancy & Pickett, 2022 ; Ferrarini et al, 2021 ; Scott et al, 2022 ; Gifford & Pickett, 2022 ). The lists of pathways were derived from publicly available versions of KEGG ( Aoki-Kinoshita & Kanehisa, 2007 ), Reactome ( Jassal et al, 2020 ), Pathway Interaction Database ( Schaefer et al, 2009 ), BioCarta, and Panther ( Mi et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…This updated algorithm retrieves additional target information, clinical trial data, automatically fetches the reactome pathway diagrams for the signaling pathways with the highest number of targets, and accepts reactome pathway enrichments generated by the enrichr algorithm ( Xie et al, 2021a ). This additional data and prioritization method are used by the updated algorithm to generate ranked lists of targets and therapeutics that can be applicable to multiple use cases ( Scott, Jensen & Pickett, 2021 ; Gray et al, 2022 ; Moreno et al, 2022 ; Rapier-Sharman, Clancy & Pickett, 2022 ). The entities in these lists can then be evaluated as candidates for condition-specific repurposing efforts based solely on the unique signaling pathway “profile” for the disease/condition of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The Pathway2Targets algorithm was then used to predict and prioritize relevant therapeutic targets from the transcriptomics signatures that could be repurposed in the case of Letrozole resistance, similar to prior work [34][35][36][37]. Briefly, this algorithm identifies known drug targets within each of the significant signaling pathways.…”
Section: Target and Biomarker Predictionmentioning
confidence: 99%